2021
DOI: 10.1590/fst.29620
|View full text |Cite
|
Sign up to set email alerts
|

Study the effect of replacing the skim milk used in making ice cream with some dried fruit

Abstract: Ice cream is a popular frozen dairy product over the world, and there are many types of ice cream that differ according to additives and manufactured way, the goal of this research was to prepare skim milk dried fruits powder (banana, quince peach, apples) for ice cream production. The chemical, physical, microbiological and sensory attributes were evaluated for resultant ice cream. As the results indicated there was an increase in the total solids of resultant ice cream, especially when using banana powder be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…The freeze concentrated has before now been applied to whey (Sánchez et al, 2011a;Canella et al, 2018), however, no replacement of milk by concentrated whey was reported in ice cream until now. Hasan et al (2020) stated that the ice cream is a popular frozen dairy product over the world, and there are many types of ice cream that differ according to additives and manufactured way. Over the past 20 years, ice cream technology has improved significantly (Al et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The freeze concentrated has before now been applied to whey (Sánchez et al, 2011a;Canella et al, 2018), however, no replacement of milk by concentrated whey was reported in ice cream until now. Hasan et al (2020) stated that the ice cream is a popular frozen dairy product over the world, and there are many types of ice cream that differ according to additives and manufactured way. Over the past 20 years, ice cream technology has improved significantly (Al et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies are interested in manufacturing dairy products in which foodstuffs are added, whether these materials are derived from milk or plant materials. Some of them are added to the manufacture of ice creams, such as dried fruits or natural sweeteners (Hasan et al, 2020;. Some of it is added in the manufacture of yogurt, such as adding dried mushroom powder, stabilizers, or different types of milk (ALKaisy et al, 2023;Al-Bedrani et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…There has been considerable academic interest in producing dairy products to which other foodstuffs have been added, whether or not these ingredients are produced from milk. such as dried fruits and natural sweeteners, are included in ice cteam industry (Hasan et al, 2020;Mulakhudairet al, 2023). Yogurt manufacturers may add dry mushroom powder, stabilizers, or various kinds of milk to the mix (ALKaisyet al, 2023; Al-Bedraniet al, 2023).…”
Section: Introductionmentioning
confidence: 99%